Telomere dysfunction in some pediatric congenital and growth-related diseases - Zheng, Bo; Fu, Jianhua (Frontiers in Pediatrics, 2023)
Telomere wear and dysfunction may lead to aging-related diseases. Moreover, increasing evidence show that the occurrence, development, and prognosis of some pediatric diseases are also related to telomere dysfunction. In this review, we systematically analyzed the relationship between telomere biology and some pediatric congenital and growth-related diseases and proposed new theoretical basis and therapeutic targets for the treatment of these diseases.